The Prognostic Value of Therapeutic Evaluation Criteria in F18 FDG PET CT In Patients with Lymphoma: Comparison Between Lesion to Liver Ratio and Visual Deauville Score - Farag, Marwa Adel; Nasr, Nourhan Kotb; Elmaghraby, Tarek Abdelfatah; Rashad, Ahmed Hamed; Tawakol, Ahmed Esameldin (Journal of Neonatal Surgery, 2025)
Background: Malignant lymphoma is regarded as the most prevalent hematological malignancy in adults and is ranked as the fourth most frequent adult malignancy, accounting for around 8.4% of all adult malignancies diagnosed yearly. Objective: To evaluate the prognostic value of TLR in 18F-FDG PET/CT in lymphoma patients and assess its role in the treatment response assessment and follow-up. Methods: This cohort analytical study involved 80 patients with 139 PET/CT study diagnosed with lymphoma (including Hodgkin and non-Hodgkin lymphoma), all referred to the Center of Clinical Oncology and Nuclear Medicine (NEMROCK) between April 2022 and May 2024. Results: TLR demonstrated excellent performance in distinguishing CMR from other outcomes, with high AUC values at interim (0.980), EOT (0.967), and follow-up (1.000) time points. Optimal TLR cut-off values were 1.111 for interim and 0.959 for EOT and follow-up assessments. TLR showed high sensitivity (75-87.50%), specificity (90.48-100%), and accuracy (85-91.94%) in predicting CMR. Significant variances in PFS have been found between patients achieving CMR and those who did not, particularly at interim (PFS: 100% vs 18.3%) and EOT (PFS: 92.4% vs 42.8%) assessments. Strong correlations were found between TLR and DS at all-time points (correlation coefficient > 0.9, p-value under 0.001). Conclusion: TLR is a valuable specific semi-quantitative measure for assessing treatment response and predicting outcomes in lymphoma patients.